2002
DOI: 10.1021/ja027130n
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Interfacial Properties of Mutually Saturated Water/1-Butanol Solutions

Abstract: Adsorption and ordering at the vapor-liquid interfaces of mutually saturated water/1-butanol solutions at a temperature of 298.15 K were investigated using configurational-bias Monte Carlo simulations in the Gibbs ensemble and compared to the surface properties of neat water and 1-butanol liquids. A dense 1-butanol monolayer is observed at the surface of the water-rich phase, which results in a substantial decrease of its surface tension. In contrast, there is no enrichment of water molecules at the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 52 publications
7
107
1
Order By: Relevance
“…10 in Lawrence et al, 2005) and argue that high mobility and density fluctuations in the butanol layer readily allow for evaporation. Our experimental temperature range ≤ 200 K and monolayer coverages, are distinctly different from the Chen et al (2002) simulations at 298.15 K, and the Lawrence et al (2005) experiments with sub-monolayer films. In our case solid ice is completely covered by the alcohol monolayers, yet still the transport rate of D 2 O from the top of the film to the subsurface ice outstrips the rate of desorption allowing nearly all of the D 2 O to quickly penetrate the alcohols.…”
Section: E S Thomson Et Al: Collision Dynamics and Uptake Of Watercontrasting
confidence: 93%
See 2 more Smart Citations
“…10 in Lawrence et al, 2005) and argue that high mobility and density fluctuations in the butanol layer readily allow for evaporation. Our experimental temperature range ≤ 200 K and monolayer coverages, are distinctly different from the Chen et al (2002) simulations at 298.15 K, and the Lawrence et al (2005) experiments with sub-monolayer films. In our case solid ice is completely covered by the alcohol monolayers, yet still the transport rate of D 2 O from the top of the film to the subsurface ice outstrips the rate of desorption allowing nearly all of the D 2 O to quickly penetrate the alcohols.…”
Section: E S Thomson Et Al: Collision Dynamics and Uptake Of Watercontrasting
confidence: 93%
“…Previous work has suggested that long-chain surfactants form well ordered impermeable domains separated by regions of more disorder where "accessible surface" exists (Barnes, 1997). For shorter chain alcohols this argument is supported by simulations that show a monolayer butanol structure is mutually beneficial for the alcohol and water due to excess hydrogen bond matching at the interface, that results in orientational ordering but compositional heterogeneity (Chen et al, 2002). Lawrence et al (2005) used this idea to explain their observation of no evaporative impediment for D 2 O leaving ≈ 80% butanol covered sulfuric acid.…”
Section: E S Thomson Et Al: Collision Dynamics and Uptake Of Watermentioning
confidence: 87%
See 1 more Smart Citation
“…This method can also be modified in order to study the liquid-liquid equilibria between two immiscible liquids [19,20]. The use of boxes with interface in the Gibbs Ensemble Monte Carlo also represents a powerful technique which enables us to study the properties of interfaces between vapor and saturated solution of two immiscible liquids [21][22][23]. Molecular Dynamics (MD) simulations in such boxes were also used in studying the free surface of alkane oligomers [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many other improvements are worth testing, such as the non-Boltzman sampling and the gradual insertion technique. With the explicit simulation of interface, it will be possible to predict interfacial tensions and achieve a detailed understanding of the role of surfactants (Goujon et al, 2001;Chen et al, 2002). In a nearby area, network calculations help to consider much larger systems (a few tens of nanometers) thereby helping to simulate micellar systems that are inaccessible with classical atomistic techniques.…”
Section: Resultsmentioning
confidence: 99%